Description of the Parasitic Nematodes (Contracaecum multipapillatum) that Infect the Intestines of (Mullus Surmuletus) Fish in the Marine Waters of Sirte-Libya - Ahmed Al-Mashai,; Omar, Muftah (AlQalam Journal of Medical and Applied Sciences, 2026)
Fish are an important food source for humans and are rich in protein, vitamins, and minerals, a number of research studies indicate that a number of parasitic injuries, including nematodes, have been recorded in different species of fish. This study aims to extract and describe the parasitic nematode Contracaecum multipapillatum, which infects Mullus surmuletus. In this study, (60) samples of Mullus surmuletus fish were collected from the seashore of the city of Sirte, located in northern Libya and on the coast of the Mediterranean Sea, 400 km east of the capital, Tripoli. The fish were collected from April to June 2022. The fish collected in the samples were transported to the Zoology Laboratory –Science Faculty –Sirte University. The fish samples were examined with the naked eye, then each sample was dissected and examined internally with a magnifying glass, and the digestive system was extracted, distributed, and examined in Petri dishes. The parasitic worms were extracted with a fine brush, described, and the male and female species were identified. The number of infected fish was also recorded. In this study, it was found that (15) Mullus surmuletus fish out of (60) fish were infected with nematodes Contracaecum multipapillatum extracted from the intestine of Mullus surmuletus fish.